Effect of replacing Soyabean meal with yellow mealworm larvae meal in a diet on performance and carcass characteristics of ross 308 broiler chicken - Tema, Matsobane Eliya (My University, 2021)
Two experiments were conducted to determine the effect of replacing soya bean meal with yellow mealworm larvae meal (Tenebrio molitor) in a diet on productivity, gut morphology, carcass characteristics and bone morphometrics of Ross 308 broiler chickens aged one to 42 days. In each experiment, a total of 360 Ross 308 broiler chickens were randomly assigned to the five dietary treatments, each treatment having four replications, and 18 chickens per replicate. Five diets were formulated to contain yellow mealworm replacement levels at 0, 25, 50, 75 and 100% to meet the nutrient requirements of Ross 308 broiler chickens. Data was analysed using the General Linear Model procedures of the Statistical Analysis System, Version 9.3.1 software program. Fisher’s least significant difference (LSD) test was applied for mean separation where there were significant differences (P<0.05). A quadratic regression model was used to determine the levels for optimal responses in the variables measured. The first experiment determined the effect of replacing soya bean meal with yellow mealworm larvae meal on productivity and gut morphology of unsexed Ross 308 broiler chickens aged one to 21 days. Replacement of soya bean meal with yellow mealworm meal in a diet had no effect (p > 0.05) on feed intake, growth rate, FCR, live body weight, ME intake and nitrogen retention of unsexed Ross 308 broiler chickens aged one to 21 days. Replacing soya bean meal with yellow mealworm meal in a diet did not affect (p > 0.05) caecum weight of unsexed Ross 308 broiler chickens. However, replacing soya bean meal with yellow mealworm meal in a diet increased (p < 0.05) gastro intestinal tract, crop, ileum and large intestine weights. Crop and ileum lengths of unsexed Ross 308 broiler chickens aged 21 days were not affected (p > 0.05) by replacement of soya bean meal with yellow mealworm meal in the diet. However, replacing soya bean meal with yellow mealworm meal in a diet increased (p < 0.05) gizzard, caecum and large intestine lengths of unsexed Ross 308 broiler chickens aged 21 days. Yellow mealworm meal in a diet did not affect (p > 0.05) gut organ digesta pH values of unsexed Ross 308 broiler chickens aged 21 days. The second experiment determined the effect of replacing soya bean meal with yellow mealworm meal in a diet on productivity, gut morphology, carcass characteristics and bone morphometrics of Ross 308 broiler chickens aged 22 to 42 days. Replacement of soya bean meal with yellow mealworm meal in a diet did not affect (p > 0.05) growth rate, FCR, ME intake and nitrogen retention of male Ross 308 broiler chickens aged 22 to 42 days. However, replacing soya bean meal with yellow mealworm meal in a diet affected (p < 0.05) feed intake and live body weight of male Ross 308 broiler chickens aged 22 to 42 days. Broiler chickens on diets containing 75 or 100% yellow mealworm meal had higher (p < 0.05) intakes than those on diets containing no yellow mealworm meal. Similarly, male broiler chickens on diets having 50% yellow mealworm meal had higher (p < 0.05) live body weights than those on diets containing no yellow mealworm. Quadratic equations indicated that feed intake and live body weight of male Ross 308 broiler chickens were optimized at yellow mealworm meal replacement levels of 13 and 61%, respectively. The present study showed that replacing soya bean meal with yellow mealworm meal in a diet did not affect (p > 0.05) gut organ digesta pH values, gut organ weights, gut organ lengths, meat colour, meat pH values, bone morphometric values, carcass part weights and meat sensory attributes of male Ross 308 broiler chickens aged 42 days. However, meat from chickens on diets containing yellow mealworm meal was softer (p < 0.05) than meat from chickens on diets having 100% soya bean meal. It is concluded that soya bean meal can be replaced with yellow mealworm larvae meal in a diet at 25, 50, 75 and 100% levels without having adverse effects on production and carcass characteristics of Ross 308 broiler chickens aged one to 42 days
Thesis (M. Sc. Agriculture (Animal Production)) -- University of Limpopo, 2021
Keywords: Yellow mealworm larvae meal; soya bean meal; Ross 308 broiler chickens, growth rate; live body weight; Gut morphology; Carcass characteristics; Meal worms; Poultry -- Feeding and feeds; Soybean